Estimación del potencial energético de los pinares de la provincia de Teruel mediante teledetección - García-Martín, Alberto; de la Riva, Juan; Pérez-Cabello, Fernando; Montorio, Raquel (Geographicalia, 2014)
The use of forest residual biomass for energy production shows many environmental and socio-economic benefits. However, the lack of a methodology to assess the regional-scale quantity of residual biomass is one of the main factors that hamper the increase in the use of this renewable resource in Spain. The present work shows a methodology to evaluate the forest residual biomass present in the pine forest of Teruel province (Spain) relating data of this biomass fraction calculated in the 1994 forest inventory with a Landsat image selected on the basis of its temporal coincidence with the inventory fieldwork. In order to avoid the influence that the heterogeneity of Mediterranean forest leads in the performance of predictive models, three different methods to extract the radiometric data are tested. The regression models derived were validated and the best equation was applied to a recent Landsat image. As a result, the potential quantity of this resource (5.449.252 tons)and an accurate distribution cartography of Teruel province were obtained.